EDUKASI SISTEM KEGAWATDARURATAN BERBASIS KEARIFAN LOKAL DI DESA MUNTEI KABUPATEN MENTAWAI PROVINSI SUMATERA BARAT - Muchsin Riviwanto; Nur Ahmad Habibi; Renidayati Renidayati; Rachmadanur Rachmadanur; Mukhlis Mukhlis; Widdeffrita Widdeffrita; Eva Yuniritha; Yosi Suryarinilsih (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Muntei Village, located in Mentawai Regency, West Sumatra, is a vulnerable area to natural disasters. However, the Mentawai community possesses rich local wisdom, including in disaster management. The objective of this community engagement is to enhance the understanding and abilities of the community in facing disasters by utilizing local wisdom. The methods employed in this community engagement include education, discussions on local wisdom, product exhibitions, and evaluations. The results of the community engagement reveal various local wisdom practices employed by the community when facing disasters, such as beliefs regarding earthquakes and rescue processes. The evaluation results indicate an improvement in the community's understanding, with the high category increasing from 40% to 80%, and the community's ability to cope with disasters improving from 20% to 83.3%. Based on these findings, it can be concluded that local wisdom in Muntei village has been passed down through generations. However, there is a need for reinforcement in the establishment of an emergency response system to ensure greater effectiveness. The provision of education is effective in enhancing the community's understanding and abilities to anticipate disasters